2013
DOI: 10.1038/pr.2013.88
|View full text |Cite
|
Sign up to set email alerts
|

1H nuclear magnetic resonance brain metabolomics in neonatal mice after hypoxia–ischemia distinguished normothermic recovery from mild hypothermia recoveries

Abstract: Background:Mild brain hypothermia (31–34 °C) after neonatal hypoxia–ischemia (HI) improves neurodevelopmental outcomes in human and animal neonates. Using an asphyxia model with neonatal mice treated with mild hypothermia after HI, we investigated whether 1H nuclear magnetic resonance (NMR) metabolomics of brain extracts could suggest biomarkers and distinguish different treatments and outcome groups.Methods:At postnatal day 7 (P7), CD1 mice underwent right carotid artery occlusion, 30 min of HI (8% oxygen), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 32 publications
0
27
0
Order By: Relevance
“…This model is classically performed in the P7 rat and is produced by unilateral common carotid ligation followed by a variable period of systemic hypoxia leading to a unilateral injury to white matter, cerebral cortex and deep nuclei (Vannucci and Vannucci, 2005). It has been adapted to younger ages (P3) (Segovia et al, 2008), to mice (Graham et al, 2004, Sheldon et al, 2007) and has been used to investigate molecular mechanisms of emerging neuroprotective therapies such as hypothermia (Liu et al, 2013) and erythropoietin (Fang et al, 2013) which are primarily targeted at term infants. Others have modified the P7 model to produce relative selectivity for white matter [but see (Selip et al, 2012)] and demonstrated a potential role for excitotoxicity in white matter injury (Follett et al, 2000, Follett et al, 2004, Manning et al, 2008).…”
Section: Modeling White Matter Injury In the Laboratory (Pre-clinicalmentioning
confidence: 99%
“…This model is classically performed in the P7 rat and is produced by unilateral common carotid ligation followed by a variable period of systemic hypoxia leading to a unilateral injury to white matter, cerebral cortex and deep nuclei (Vannucci and Vannucci, 2005). It has been adapted to younger ages (P3) (Segovia et al, 2008), to mice (Graham et al, 2004, Sheldon et al, 2007) and has been used to investigate molecular mechanisms of emerging neuroprotective therapies such as hypothermia (Liu et al, 2013) and erythropoietin (Fang et al, 2013) which are primarily targeted at term infants. Others have modified the P7 model to produce relative selectivity for white matter [but see (Selip et al, 2012)] and demonstrated a potential role for excitotoxicity in white matter injury (Follett et al, 2000, Follett et al, 2004, Manning et al, 2008).…”
Section: Modeling White Matter Injury In the Laboratory (Pre-clinicalmentioning
confidence: 99%
“…For example, 1 H-NMR has been used to uncover specific highly abundant metabolites (N-acetyl-aspartate, myo-inositol, glutamate, glutamine, creatine, choline and GABA). Such studies have proven to be a key for the characterization of neurochemical and metabolic profiles relevant to brain health (Davidovic, et al, 2011; Liu, et al, 2013; Pears, et al, 2005; Prabakaran, et al, 2004; Tkac, et al, 2004). Granting high reproducibility, the MR technologies are restricted by their low sensitivity, which hinders comprehensive pathologic assessments.…”
Section: Introductionmentioning
confidence: 99%
“…Hypoxia-ischaemia leads to alterations in cellular energy pathway molecules, such as glycerol and succinate, via mitochondrial dysfunction and subsequent disruption of the tricarboxylic acid cycle [22]. Altered O-phosphocholine has been described in animal models of hypoxia-ischaemia [23]. It is both an anabolic and catabolic metabolite of cell membrane metabolism and may indicate, along with glycerol, cellular membrane breakdown [24].…”
Section: Discussionmentioning
confidence: 99%